The Impact of Resistant Bacterial Pathogens including Pseudomonas aeruginosa and Burkholderia on Lung Transplant Outcomes - Mitchell, Alicia B.; Glanville, Allan R. (Seminars in Respiratory and Critical Care Medicine, 2021)
Pseudomonas and Burkholderia are gram-negative organisms that achieve colonization within the lungs of patients with cystic fibrosis, and are associated with accelerated pulmonary function decline. Multidrug resistance is a hallmark of these organisms, which makes eradication efforts difficult. Furthermore, the literature has outlined increased morbidity and mortality for lung transplant (LTx) recipients infected with these bacterial genera. Indeed, many treatment centers have considered Burkholderia cepacia infection an absolute contraindication to LTx. Ongoing research has delineated different species within the B. cepacia complex (BCC), with significantly varied morbidity and survival profiles. This review considers the current evidence for LTx outcomes between the different subspecies encompassed within these genera as well as prophylactic and management options. The availability of meta-genomic tools will make differentiation between species within these groups easier in the future, and will allow more evidence-based decisions to be made regarding suitability of candidates colonized with these resistant bacteria for LTx. This review suggests that based on the current evidence, not all species of BCC should be considered contraindications to LTx, going forward.
Keywords: lung transplantation; Pseudomonas; Burkholderia; cystic fibrosis; sepsis